Answer:
y = x + 6
Step-by-step explanation:
y = x + b
when x = 0, y = 6. so....
6 = (0) + b
6 = b
so, y = x + 6
Answer:
x-int : 6, y-int : 9
Step-by-step explanation:
Hope this helps :)
Let me know if you want a full explanation
Answer:
Step-by-step explanation:
From the given right-angle triangle
The angle = ∠60°
-
The adjacent to the angle ∠60° is 1/2.
- The opposite to the angle ∠60° is y.
The hypotenuse = x
<u>Determining the value of x:</u>
Using the trigonometric ratio
cos 60° = adjacent / hypotenuse
substituting adjacent = 1/2 and hypotenuse = x


∵ cos (60°) = 1/2

Dividing both sides by 2

Simplify

Thus, the value of hypotenuse x is:
x = 1
<u>Determining the value of y:</u>
Using the trigonometric ratio
sin 60° = opposite / hypotenuse
As we have already determined the value of hypotenuse x = 1
substituting opposite = y and hypotenuse = 1
sin 60° = y/1
y = 1 × sin 60°
∵ 
Therefore, the value of y is:
Summary:
I can't see the whole graph
-10 = -10 + 7m
Add 10 to each side: 0 = 7m
Divide each side by 7 : 0 = m
Please take a second and just LOOK at the equation you started with.
It says:
-- You have this number '-10' .
-- Your number -10 is going to be exactly the same size
after you add 7 of something to it.
The ONLY way that could happen is if the 'something' is 'nothing' .
' m ' must be nothing.